2023
DOI: 10.1128/jvi.00228-23
|View full text |Cite
|
Sign up to set email alerts
|

Combinational Deletions of MGF110-9L and MGF505-7R Genes from the African Swine Fever Virus Inhibit TBK1 Degradation by an Autophagy Activator PIK3C2B To Promote Type I Interferon Production

Abstract: African swine fever (ASF) is a contagious and lethal hemorrhagic disease of pigs caused by the African swine fever virus (ASFV), leading to significant economic consequences for the global pig industry. The development of an effective and safe ASF vaccine has been unsuccessful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 59 publications
1
3
0
Order By: Relevance
“…This study provided the first evidence of the role of the MGF300-2R gene, for which the function was unknown. We analyzed whether there are differences in binding, internalization, virus particle release, and viral factory formation between the Del2R and ASFV-WT, but no significant differences were observed (S3 Fig) . Recently, it has been found that the MGFs (MGF110-9L, MGF360-9L, and MGF505-7R) are involved in ASFV virulence and immune evasion [13][14][15][16]. We observed an increase in the expression levels of the NF-κB mediated proinflammatory cytokines IL-1β and TNF-α in the Del2R-infected PAMs, as indicated using RNA-seq, RT-qPCR, and ELISA analysis (Fig 2).…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…This study provided the first evidence of the role of the MGF300-2R gene, for which the function was unknown. We analyzed whether there are differences in binding, internalization, virus particle release, and viral factory formation between the Del2R and ASFV-WT, but no significant differences were observed (S3 Fig) . Recently, it has been found that the MGFs (MGF110-9L, MGF360-9L, and MGF505-7R) are involved in ASFV virulence and immune evasion [13][14][15][16]. We observed an increase in the expression levels of the NF-κB mediated proinflammatory cytokines IL-1β and TNF-α in the Del2R-infected PAMs, as indicated using RNA-seq, RT-qPCR, and ELISA analysis (Fig 2).…”
Section: Discussionsupporting
confidence: 58%
“…A viral protein can play a regulatory role at different levels of the NF-κB and IFN signaling pathways. For example, the virulence-associated protein MGF505-7R of ASFV can interact with IKKα and multiple adaptors of the IFN signaling pathway, including STING, IRF9, IRF3, JAK1, and JAK2 to inhibit IL-1β and IFN production, respectively [13][14][15][16]49]. Recently, numerous studies have demonstrated that the IFN inhibitors of ASFV are likely to influence viral replication and pathogenicity [50].…”
Section: Plos Pathogensmentioning
confidence: 99%
See 2 more Smart Citations